PENGATURAN PEMBERIAN HAK REMISI BAGI NARAPIDANA DI INDONESIA, STUDI KOMPARASI DENGAN BEBERAPA NEGARA LAIN DI DUNIA - Nugraha Bimasakti, R. Aditayoga (Jurnal Aktual Justice, 2022)
The regulation of remission rights for prisoners in Indonesia refers to The Republic of Indonesia Law No. 12 of 1995 about Corrections and their derivative regulations, namely The Government of the Republic of Indonesia Regulation No. 99 of 2012 about The Second Amendment to The Republic of Indonesia Government Regulation No. 32 of 1999 about the Terms and Procedures for the Implementation of the Rights of Correctional Inmates and The Decree of the President of the Republic of Indonesia No. 174 of 1999 about Remissions. In these provisions, it regulates general conditions for prisoners to obtain remission rights and special conditions in certain criminal acts for prisoners to obtain remission. This then raises the pros and cons of tightening the granting of remission rights for convicts of certain crimes in Indonesia. If this is compared with several other countries in the world, it can be concluded that there are countries that also regulate tightening in the granting of remission rights for prisoners, while those that provide remissions equally regardless of the type of crime committed by the inmates, depending on the policies of each country. Therefore, Indonesia should in drafting provisions regarding tightening the granting of remission rights for inmates must carefully consider the reasons for the pros and cons that occurred, so that the rules created do not cause continuous polemics. This writing aims to provide new contributions to science to be published using normative research methods.